Conociendo algunas expresiones del español colombiano. (2020)
CONOCIENDO ALGUNAS EXPRESIONES DEL ESPAÑOL COLOMBIANO, is a website that is meant to achieve to foreigners learn expressions from some Colombian cities autonomously and use them in real contexts. This has videos made by people from the selected cities, in addition to the manifestation of expressions are presented with examples of their meanings, accompanied by activities presented in a dynamic way with content related to the subject of teaching.